The association between differentiation of self and romantic relationship outcomes and the mediating role of communication behaviors - Wilson, Christina Emma (Kansas State University, 2020)
This study examined the association between level of differentiation of self on romantic relationship outcomes (i.e., attachment, relationship satisfaction, and gridlock) while, additionally, examining the possibility of communication (i.e., validation and withdrawal) as a mediator. Participants (N = 463) were recruited using Amazon’s Mechanical Turk (MTurk) to complete an online survey and had to be in a committed romantic relationship to be eligible. After controlling for psychological distress, relationship length, and gender, the results indicated a significant and direct relationship between differentiation and relationship outcomes and an indirect relationship through validation and withdrawal. Specifically, differentiation was directly, negatively associated with gridlock (β = -16, p = .003), avoidant attachment (β = -.13, p = .032), and anxious attachment (β = -.51, p < .001). In addition to these direct associations, differentiation was also indirectly associated with gridlock and avoidant attachment through both validation and withdrawal. On the other hand, differentiation was only indirectly associated with relationship satisfaction through validation (β = .44, p < .001). Additionally, we tested an alternate model with attachment and differentiation as predictors of relationship satisfaction and gridlock, and, again, examined validation and withdrawal as mediators. Results indicated that our primary model was a slightly better fit to the data than this alternative model, supporting the idea that attachment can be seen not only as a predictor but also as a relationship outcome. These results suggest that differentiation might be usefully accessed through more overt communication behaviors, which in turn might be related to having desired relationship outcomes.
Keywords: differentiation; communication behaviors; relationship outcomes